We are all completely beside ourselves [large type] - Fowler, Karen Joy (Center Point Large Print, 2013)
Coming of age in middle America, eighteen-year-old Rosemary evaluates how her entire youth was defined by the presence and forced removal of an endearing chimpanzee who was secretly regarded as a family member and who Rosemary loved as a sister.